Management of Febrile Urinary Tract Infection With or Without Bacteraemia in Children: A French Case-Control Retrospective Study - Goeller, Caroline; Desmarest, Marie; Garraffo, Aurélie; Bonacorsi, Stéphane; Gaschignard, Jean (Frontiers in Pediatrics, 2020)
Background: Febrile urinary tract infections (FUTIs) are common among children, and are associated with a bacteraemia between 4 and 7% of cases. No data is available concerning the management of children with a bacteraemic FUTI. Objectives: To compare the antibiotic treatment (parenteral and total duration) among children with bacteraemic and non-bacteraemic FUTIs, the mean hospital length of stay (LOS) and the outcome; to describe clinical, microbiological and imaging features of children with bacteraemic and non-bacteraemic FUTIs and observed management modifications when the blood culture was positive. Methods: A retrospective case-control study between 2009 and 2015 at Robert Debré’s Paediatric Emergency Department (Paris, France). Children aged <18 years with a bacteraemic FUTI were included and matched for age and sex with two children with a non-bacteraemic FUTI. Results: We included 50 children with a bacteraemic FUTI matched to 100 children with a non-bacteraemic FUTI. Clinical features at presentation were comparable. Bacteraemic patients had a higher procalcitonin (p=0.006) and C-reactive protein (p=0.01). The mean duration of parenteral antibiotics and mean LOS were longer for bacteraemic compare to non-bacteraemic children (6.7 vs. 4.0 days, p<0.001 and 5.1 vs. 2.0 days, p<0.001 respectively) but these differences were only significant in children > 28 days-old. The mean total duration of antibiotic was similar (11.3 vs. 11.6 days, p=0.61). A positive blood culture changed the management in 66% of patients but outcome was similar in both groups. Conclusions: A bacteraemic FUTI induced a longer duration of parenteral antibiotic treatment and a longer hospitalization in children > 28 days-old, and a modification of management for 66% of patients without significant difference in outcome.